Regulation of heavy metals accumulated by Acorus calamus L. in constructed wetland through different nitrogen forms. (October 2021) - Wang, Jun-Feng; Zhu, Cong-Yun; Weng, Bai-Sha; Mo, Pei-Wen; Xu, Zi-Jie; Tian, Ping; Cui, Bao-Shan; Bai, Jun-Hong
Abstract: Improving accumulation of heavy metals (HMs) by plants is an important pathway for constructed wetland (CW) to alleviate the environmental risks caused by their release. This study aims to regulate HMs (Cr, Ni, Cu, Zn, and Cd) accumulated by Acorus calamus L. in the sandy substrate CW with different nitrogen forms, including ammonia (NH4 + ), nitrate (NO3 ‾), and NH4 + /NO3 ‾ (1:1) in synthetic tailwaters. In general, the removal efficiency of HMs by CW could reach 92.4% under the initial concentrations below 500 μg/L. Accumulation percentages of HMs in the shoots and roots of plants in CW with NH4 + and NH4 + /NO3 ‾ influents increased by 52–395% and 15–101%, respectively, when compared with that of NO3 ‾ treatment. Influents with NH4 + promoted plant growth of Acorus calamus L. and metabolic functions, such as carbohydrate metabolism/amino acid metabolism, related to HMs mobilization of rhizosphere bacterial communities, which might induce more organic acids and amino acids secreted by plants and microbes during their metabolic processes. These are the main reasons for the enhancive mobilization of HMs from their precipitation fractions and their uptake by plants in CW with NH4 + treatments. Moreover, the enhancement of organics secreted from plants and microbes also led to the high denitrification efficiency and nitrogen removal in CW. Overall, this study could provide a feasible method for the enhancive accumulation of HMs by wetland plants via the regulation water treatment process to appropriately increase NH4 + for CW. Graphical abstract: Image 1 Highlights: Nitrogen removal efficiency increased with enhancive root exudates from plants. Quantity of HMs uptake by plants with NH4 + was 48–175% higher than that of NO3 ‾. NH4 + and NO3 ‾ induced different microbial communities in rhizosphere sand of CW. NH4 + up-regulated the expression of bacterial genes related to HMs mobilization in CW.